Perancangan aplikasi reservation room pada hotel xyz di Indramayu - Sumardiono; Sofyan Efendi; Hadi Santosa (INFOTECH : Jurnal Informatika & Teknologi, 2022)
Management for a business or business is really needed, including management in the hotel environment related to room reservations or room reservations. Room reservations made by consumers at a hotel are administrative matters, so it is necessary to have records or data that need to be stored and retrieved with the aim of being more useful information for the management. This research is an applied research that applies a system development method in the form of the SDLC (Software Development Life Cycle) method with the application of a prototype model. As for data acquisition, researchers use literature studies, observations, and interviews to obtain data in the form of problems that occur, and are called primary data. Meanwhile, in the application of the method using a prototype model, it is carried out in 3 phases, namely the planning phase (data analysis), the design and implementation phase, and the system evaluation phase. The results of this study are in the form of e-reservation room software that was tested in offline conditions. Hope this research can help the management at xyz hotel, especially in serving hotel room reservations.